2008
DOI: 10.1021/la7028214
|View full text |Cite
|
Sign up to set email alerts
|

Surface Stress, Thickness, and Mass of the First Few Layers of Polyelectrolyte

Abstract: The effects of surface stress and mass loading upon the adsorption of polyelectrolytes onto flexible silicon micromechanical cantilever sensors (MCSs) were studied in situ. A self-assembled monolayer of 2-mercaptoethylamine chloride (2-MEA) on gold was used to achieve single-side adsorption on the MCS. Such a preparation gave a positive surface potential, whereas a bare SiOx surface gave a negative surface potential. Wide scan X-ray photoelectron spectroscopy confirmed that the adsorption of polystyrenesulfona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 44 publications
2
10
1
Order By: Relevance
“…However, the average thickness increase is 1.8 ± 0.3 nm and 7.0 ± 1.3 nm per bilayer for the salt-free PE solutions and in the presence of 0.15 M NaCl, respectively. These values differ from previously published data for LbL coating of planar substrates, where the average thickness per PE layer was ~1–3 nm 23 , 31 33 . We attribute this discrepancy to different hydrodynamic conditions for PE adsorption in our study 22 and the effect of the charged capillary surface.…”
Section: Resultscontrasting
confidence: 99%
“…However, the average thickness increase is 1.8 ± 0.3 nm and 7.0 ± 1.3 nm per bilayer for the salt-free PE solutions and in the presence of 0.15 M NaCl, respectively. These values differ from previously published data for LbL coating of planar substrates, where the average thickness per PE layer was ~1–3 nm 23 , 31 33 . We attribute this discrepancy to different hydrodynamic conditions for PE adsorption in our study 22 and the effect of the charged capillary surface.…”
Section: Resultscontrasting
confidence: 99%
“…In contrast the 5th and 6th line (fig. 4.46) are quite homogenous and the thickness of 70 nm and 65 nm scales with 3 nm per BL which was found in previous studies [135] for the classical LbL process by x-ray reflectivity using a salt concentration of 1 mol/L. In this case the liquid did not evaporate completely and had a contact time of 3 to 6 s. So it can be concluded that it is important to keep a minimum adsorption time which is limited by the total evaporation time of the solvent.…”
Section: Printing Pem Line Structuressupporting
confidence: 74%
“…The change in stress within the swollen ppAA film could be calculated from the deflection magnitude of MCS using Stoney's formula . Within the entire H range from 10 to 80%, we measured a larger stress change for the ppAA film deposited at 90 W compared with that deposited at 5 W (Figure ).…”
Section: Resultsmentioning
confidence: 83%